Violent maritime spaces: Conservation and security in Gulf of Mannar Marine National Park, India. (June 2020) - Muralidharan, Rahul; Rai, Nitin D.
Abstract: The militarisation of conservation involves the integration of conservation, security and counterinsurgency through violent and armed strategies, or 'war, by conservation'. We describe a militarised conservation practice in which a marine protected area was established by the state and supported by international actors in a region of ongoing ethnic and military conflict as a case of conservation, by war. Conservation and security actors actively criminalise artisanal fishing communities in Gulf of Mannar Marine National Park in India. The harvest of sea cucumbers, marine species of commercial value historically traded between the Indian state of Tamil Nadu and Sri Lanka, was banned and has become the target of militarised action. When the Sri Lankan civil war broke out in 1983, sea cucumber trade turned into a security concern as the same sea routes were also being used for trafficking arms, ammunition, and other contraband. Tamil Nadu was geographically and logistically involved in the civil war due to ethnic ties. The Sri Lankan civil war and its social and political consequences on the neighbouring state of Tamil Nadu due to ethnic ties is a fitting case of the nexus of conservation and security in a marine context. Based on ethnographic fieldwork and interviews conducted with artisanal fishers and conservation and security actors, we show that violent political conflict provided the justification for securitisation of conservation. As the state focuses its conservation efforts on the marine protected area, commercial fisheries detrimental to fisheries and biodiversity conservation continue. Marine protected areas allow the state to achieve its security outcomes even as it fails to meet its conservation goals due to non-local drivers of declines in species populations. Trans-boundary marine environments are particularly difficult to govern due to the dynamic nature of the seascape. The materiality of the sea and the conservation-security nexus results in the creation of a violent maritime space.